Variations in the patients' hospital care experience by states' strategy for Medicaid expansion: 2009-2013 - Edmund Becker; Kenton Johnston; Jaeyong Bae; Jason Hockenberry; Ariel Avgar; Sandra Liu; Ira Wilson; Arnold Milstein (The Beryl Institute, 2015)
Our investigation evaluates the extent of differences in the patient's hospital experience due to variations among state strategies to adopt, or not adopt, their Medicaid plans to the 2010 ACA legislation. Using ten HCAHPS measures, we analyze patient hospital experience data for the 2009 - 2013 period for all 50 states and the District of Columbia grouped by those states that (1) did not expand, (2) expanded Medicaid through Section 1115 waivers, (3) expanders early, and (4) expanded Medicaid concurrent with the new ACA legislation. Our findings reveal that those states that opted out of Medicaid expansion typically started with higher patient experience scores in 2009 on all 10 HCAHPS hospital measures and maintained their higher scores levels for all five years over the other three state expansion strategies for most measures. While states that were early expanders and those that expanded concurrent with the ACA implementation generally show higher growth rates over the five-year period for most HCAHPS measures when compared to states that opted out of the Medicaid expansion, our multivariate results indicate that their rates of growth were not statistically superior to those states that opted out of the expansion. We conclude that while there have been concerns that the patients in opt-out states would experience lower levels of satisfaction from their state's actions, the patient experience scores in these states show that they perform better or as well as those states that expanded early, expanded under waivers, and expanded with the implementation of the ACA legislation.